Intelligent control of an UAV - Chong, Abel Weng Lok (2015)
This project entailed design and testing of an autonomous indoor quad rotor UAV. The project will take part 2015 Singapore Amazing Flying competition which will be held in March 2015. The challenge in this competition is make an autonomous UAV to cross obstacles, recon and drop payloads at target area. The quad-copter has multiple degrees of freedom, rotation ability and multiple add-on functions. The propulsion system produces 4kg of thrust using 14" propellers. The UAV carries a variety of sensors such as a laser rangefinder, sonar and infrared sensors. These sensors are interfaced to on-board processors, which send high-level commands to a low-level flight controller. Flight tests were conducted to demonstrate the flight control and sensor operation of the UAV.